2012
DOI: 10.1177/008124631204200102
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Generalised Anxiety and Psychomotor Test Performance in Healthy South Africans

Abstract: Tests like the Grooved Pegboard may have specific value in South Africa in the context of screening for HIV-associated neurocognitive disorders. However, there are inconsistent findings on the relationship between self-reported anxiety and neuropsychological performance in healthy adults, and in particular on tests of psychomotor functions such as the Form Board and Grooved Pegboard. Given the potential value, it is important to clarify the relationship between self-reported anxiety and performance on psychomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…In contrast to the above, self-report generalised anxiety does not appear to meaningfully affect GPT performance in healthy adults (Van Wijk, 2012;Waldstein, Ryan, Jennings, Muldoon, & Manuck, 1997;Wassermann, Greenberg, Nguyen, & Murphy, 2001).…”
contrasting
confidence: 82%
See 1 more Smart Citation
“…In contrast to the above, self-report generalised anxiety does not appear to meaningfully affect GPT performance in healthy adults (Van Wijk, 2012;Waldstein, Ryan, Jennings, Muldoon, & Manuck, 1997;Wassermann, Greenberg, Nguyen, & Murphy, 2001).…”
contrasting
confidence: 82%
“…The effect of gender is less consistent. Some studies found that women perform noticeably faster than men (Bryden & Roy, 2005; Polubinski & Melamed, 1986; Van Wijk, 2012), and greater inter-manual differences for females compared to males were reported (Thompson, Heaton, Matthews, & Grant, 1987). One study found significant gender differences for the dominant hand (DH) only (Schmidt, Oliveira, Rocha, & Abreu-Villaca, 2000), while another did not find any significant gender difference (Strenge, Niederberger, & Seelhorst, 2002).…”
mentioning
confidence: 99%